Dampak Interaksi Remaja dengan Lingkungan Digital: Emosi Perilaku, dan Pengaruhnya - Laeli Shifa Nur Fauziah (BADAN PENERBIT STIEPARI PRESS, 2023)
These studies each explore important aspects of the relationship between adolescents, their emotions, behavior, and environments. The first study highlighted the negative impact of playing esports games on teenagers' emotions and learning achievement. The second study showed a negative relationship between emotional maturity and aggressive behavior in vocational school students. The third study emphasizes the significant relationship between emotional stability and self-control in junior high school students. The fourth study revealed the negative impact of verbal violence perpetrated by parents on children, including emotional disturbances, increased aggression, and damage to children's self-concept. The fifth research aims to determine the relationship between emotional intelligence and juvenile delinquency among students at Sudirman Islamic Vocational School, West Ungaran District, Semarang Regency. Finally, the sixth research aims to analyze the influence of economic pressure and parent-adolescent interactions on the social emotional development of adolescents in families living in Rusunawa West Jatinegara. All of this research provides a deeper understanding of these issues and the importance of a thoughtful approach to educating and understanding adolescents.